Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12889-017-4998-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of employer financial incentives in reducing time to report worker injury: an interrupted time series study of two Australian workers’ compensation jurisdictions

Abstract: BackgroundEarly intervention following occupational injury can improve health outcomes and reduce the duration and cost of workers’ compensation claims. Financial early reporting incentives (ERIs) for employers may shorten the time between injury and access to compensation benefits and services. We examined ERI effect on time spent in the claim lodgement process in two Australian states: South Australia (SA), which introduced them in January 2009, and Tasmania (TAS), which introduced them in July 2010.MethodsU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…ERIs were introduced as a policy in 2009 in South Australia, encouraging employers to report worker injuries in a timely fashion. Employers who lodged a compensation claim within two working days of becoming aware of an injury were given a rebate on their insurance excess [15]. Results for the regression models were expressed as rate ratios (RR) with 95% confidence intervals (CIs) by exponentiating the coefficients and interpreting them as a percentage change in compensation expenditure or working days lost with change of age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ERIs were introduced as a policy in 2009 in South Australia, encouraging employers to report worker injuries in a timely fashion. Employers who lodged a compensation claim within two working days of becoming aware of an injury were given a rebate on their insurance excess [15]. Results for the regression models were expressed as rate ratios (RR) with 95% confidence intervals (CIs) by exponentiating the coefficients and interpreting them as a percentage change in compensation expenditure or working days lost with change of age.…”
Section: Methodsmentioning
confidence: 99%
“…In the process of deindustrialisation, a gradual decline in work-related morbidity and mortality has also been observed in other developed countries such as USA [22] and Canada [23]; and (3) the tightening eligibility for compensation benefits overtime. Evidence has shown that the level of compensation benefits was positively associated with claim rate [15,24]. In addition, the trend might be confounded by the introduction of ERIs in 2009, although there is limited research to investigate its impact on injury claims.…”
Section: A Downward Trend: Implications For Intervention Effectivenesmentioning
confidence: 99%
“…Consistent with the policy objectives of the reforms, we hypothesise a reduction in the number of workers accessing the NSW workers’ compensation scheme in the period after reform. Based on prior studies that have demonstrated increases in the time taken by insurers to adjudicate claims following legislative reform,17 and the adverse impacts of slower decision making on return to work,4 5 we hypothesise that the reforms increased insurer decision time and the duration of disability among workers with accepted claims. Finally, we hypothesise that workers with occupational disease and mental health conditions will be disproportionately affected by the reforms.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of penalties for late workplace injury reports was implemented because of both recommendations set out in Clayton's report and research that indicates long lag times are associated with poorer RTW outcomes and higher costs to the WC system (Workers Rehabilitation and Compensation Amendment Bill, Tasmanian Government 2009). In an earlier study, we found that whilst claim reporting time significantly dropped in Tasmania, insurer decision time increased (attributed to administrative burden of implementing a whole suite of amendments), which offset the gains, leading to no change in the time between injury and acceptance of claim (Lane et al 2018). This shows that there can be unintended consequences of changing legislation, in this case possibly because the system could not handle claims in the same manner as before the change.…”
Section: Discussionmentioning
confidence: 77%